MEMPROMOSIKAN OLAHRAGA UNTUK PENINGKATAN KESEHATAN MASYARAKAT - Agung Dwi Darmawan; Jalu Amin Angkasa Mudiana Putra; Suhartik (STAND, 2023)
Sport is one thing that is very important in supporting public health. The decline in public awareness of sports is one of the things that is the focus of this paper. Social change in society becomes more advanced when all levels of society are involved in sports. In RI Law no. 3 of 2005 concerning the National Sports System provides legal certainty for the public in exercising to create an active, healthy, fit and accomplished nation. Some of these social changes include living healthier with less disease, becoming fitter, increasing harmony in community relations, increasing the spirit of competition and sportsmanship within the community itself. Using a descriptive qualitative approach, this article will explain in detail how to increase people's interest in exercising again. Coercive strategy (Coercive), consisting of: Pressure strategy (pressure). Normative strategy, consisting of participation strategy, education and training strategy. Benefits strategy Placement strategy. If sport has become a culture in society, then people don't have to be forced to do sports, people will also learn in more detail about the goals of sports and how to do sports that are good and right to improve health status.